Contemporary challenges in administrative law and public administration : contributions to International Conference "Contemporary Challenges in Administrative Law and Public Administration", April 27, 2018, Bucharest - Szczepaniak, Rafal; Figueiras, Cláudia Sofia Melo (Adjuris - International Academic Publishers, 2018)
This volume contains the scientific papers presented at the International Conference "Contemporary Challenges in Administrative Law and Public Administration" that was held on 27 April 2018 at Bucharest University of Economic Studies, Romania. The scientific studies included in this volume are grouped into two chapters: Contemporary Challenges in Administrative Law and Contemporary Challenges in Public Administration.